Brain Patents as a Legal or Societal Challenge? - Tade Matthias Spranger (IIC - International Review of Intellectual Property and Competition Law, 2023)
Patents relating to the human brain and its functions regularly fulfil the general patent requirements. In some cases, however, the inventions in question reveal considerable risks for the rights of individuals, but also for society as such, which have a hitherto unknown dimension and which have not been discussed so far. Due to the limited scope of application of the ordre public clause, patent law is fundamentally not in a position to respond adequately to the challenges that exist here. The ratio of patent law and the lack of resources and also, above all, competence of the patent offices for a more extensive ethico-legal analysis mean that patent law is not the right setting for dealing with the existing challenges. Instead, the international organisations responsible for the protection of human rights and their relevant bodies are in particular demand here, although they have so far been unaware of the difficulties that are evident in the area of brain patents. What is needed is the development and establishment of mechanisms that enable the flagging and communication of critical patents, so that the responsible bodies are enabled to fulfil their tasks.
Keywords: 340; Brain patents; Neurolaw; Neuroethics; Human rights; Ordre public; Misuse